INTERPRETASI MEDIA LUAR RUANG IKLAN ROKOK DAN POLA HIDUP SEHAT MASYARAKAT DESA SALUASSING - Yunalpi Yunalpi; Muhammad Syaeba; Ulya Sunani (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Al Asyariah Mandar, 2021)
This study aims to determine the public's interpretation of the outdoor media for cigarette advertising and the healthy lifestyle of the people of Sawidesing Village. The research method used is descriptive qualitative method. Data were obtained through interviews, surveys, and documentation. The results showed that the outdoor media for cigarette advertising is a very helpful message in bridging the understanding of the existence of a cigarette product, especially useful on the sales side. Meanwhile, regarding cigarettes and their healthy lifestyle, smoking is a part of life that really helps all their daily activities. Cigarettes actually become an element that makes citizens always healthy in their activities from young to old.